Cloxacillin-resistant staphylococci in a children's hospital - Skirrow, M. B. (1971)
Two hundred and thirty-seven selected, penicillin-resistant isolates of Staph. aureus collected over a 13-month period were examined retrospectively for cloxacillin/methicillin resistance; 44 were found to be resistant. Six other strains which had been preserved from an earlier period were also found to be resistant. All 50 cloxacillin-resistant strains were in addition resistant to streptomycin and several other antibiotics. According to their resistance patterns and reactions to phages, they could be classified into two categories. The proportion of cloxacillin-resistant strains among the total number of staphylococci isolated during the 13-month period was estimated to be 2·7%. Children most at risk from infection were those undergoing long-term hospital treatment and on several occasions children transferred from other hospitals in the region were found to be carrying resistant strains. Most infections caused by these strains were minor but they were nevertheless capable of producing severe illness and they were responsible for 33% of all staphylococcal wound infections.